PRESENT AND ANCIENT LANDFORMS OF THE MEZHYRYCH GEOARCHEOLOGICAL SITE - BORTNYK, Sergii; POHORILCHUK, Nataliia; KOVTONIUK, Olga (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Comprehensive geoarchaeological studies of prehistoric and historic human settlements involve analyzing all components of the ancient natural environment, including topography and landforming processes. However, insufficient attention to documenting these crucial characteristics, as well as arbitrary use of geomorphological terms, complicates their further interpretation. The research aims to revise existing geomorphological descriptions and paleogeomorphological reconstructions of the Mezhyrich geoarchaeological site, refining and detailing its position within the modern and ancient land surface structure. Methods. The research was conducted using cartographic methods and decoding materials from aerial photography. Additionally, a thorough bibliographic analysis of scientific publications related to paleogeographical reconstructions of the study area was carried out. Results. Discrepancies have been identified in precisely determining the geomorphological context of this site. The study delves into contentious issues surrounding various approaches to numbering the floodplain terraces. These debates stem from the use of different stratigraphic schemes for Ukraine’s Quaternary deposits when dating alluvium. Additionally, the debate extends to criteria for terrace numbering. Through the analysis of satellite imagery, hypsometric and geomorphological diagrams, and other geological-geomorphological materials, the contemporary geomorphological situation has been refined, and the peculiarities of the ancient terrain have been unearthed. The role of morphostructural position, the spectrum of processes, and the dynamics of morpholithogenesis have been pinpointed. Conclusions. The conducted research substantiates the pivotal role of terrain in the selection and organization of safe living spaces for ancient humans. To address the issue of linking the Mezhyrich geoarchaeological site to the terrace level, the proposal is to number the terraces based on morphological features, thereby avoiding divergent interpretations of the ages of correlated deposits and discrepancies in terrace designations. Furthermore, there is potential for utilizing the geomorphological information from the investigated Late Paleolithic settlement as a search criterion for locating other ancient human settlements under similar physiogeographic and geological-structural conditions.